Assessment and remediation of pollutants in Ghana's Kete-Krachi District Hospital effluents using granular and smooth activated carbon. Issue 7 (July 2018) - Tulashie, Samuel Kofi; Kotoka, Francis; Kholi, Foster Kwame; Aggor-Woananu, Samira Esinam Elsie; Tetteh, Gifty Rhodalyn
Abstract: The need for simple, cheaper and high performance hospital effluent treatment system in Kete-Krachi District which is adjacent to the Lake Volta has necessitated this study. This study focuses on assessing, and treating Kete-Krachi District Hospital effluent using packed granular (GAC) and smooth activated carbon (SAC). The use of activated carbon is due to its less expensive method of operation, the ease to prepare from local raw materials, high availability, and effectiveness for treating hospital effluent. The dissolved oxygen (DO), chemical oxygen demand (COD), biochemical oxygen demand (BOD), nutrient compounds (P-PO4, N-NO3 ), turbidity, pH, conductivity and total coliform parameters were investigated and later treated with the activated carbon. The average conductivity and P-PO4 removals were <50%. The average BOD5, COD, coliform, N-NO3, and turbidity removals for all the SAC treatments were 58.36%, 62.26%, 84.39%, 83.86%, and 50.74%, respectively. The DO also improved 3.8 times on the average. The pH of the raw and treated samples was within the limit 6.5–9. The results of this study suggest that the SAC is predominantly effective for reducing the pollutants concentrations of the hospital effluent which can result in oxygen depletion, eutrophication, algal bloom and ecosystem disturbance in the Lake Volta. It will also decrease the susceptibility of the Kete-Krachi residents to waterborne diseases as the effluents seep into the Lake.